2011
DOI: 10.1016/j.nima.2011.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Scintillation decay time and pulse shape discrimination in oxygenated and deoxygenated solutions of linear alkylbenzene for the SNO+ experiment

Abstract: The SNO+ liquid scintillator experiment is under construction in the SNOLAB facility in Canada. The success of this experiment relies upon accurate characterization of the liquid scintillator, linear alkylbenzene (LAB). In this paper, scintillation decay times for alpha and electron excitations in LAB with 2 g/L PPO are presented for both oxygenated and deoxygenated solutions. While deoxygenation is expected to improve pulse shape discrimination in liquid scintillators, it is not commonly demonstrated in the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 9 publications
4
48
0
Order By: Relevance
“…This work found that the slow component of an exponential decay of the scintillation is stronger pronounced at lower temperatures. As the triplet lifetime of benzene matches this slow decay component well [21][22][23][24], this result can be seen as an indication that either more triplet states are populated or that the radiative de-excitation of those is more efficient at lower temperatures. The increased population would fit into the theory of Birks and Conte [9,25], who proposed that the energy transfer between solvent-solvent and solvent-solute molecules is mainly due to excimer formation.…”
mentioning
confidence: 67%
“…This work found that the slow component of an exponential decay of the scintillation is stronger pronounced at lower temperatures. As the triplet lifetime of benzene matches this slow decay component well [21][22][23][24], this result can be seen as an indication that either more triplet states are populated or that the radiative de-excitation of those is more efficient at lower temperatures. The increased population would fit into the theory of Birks and Conte [9,25], who proposed that the energy transfer between solvent-solvent and solvent-solute molecules is mainly due to excimer formation.…”
mentioning
confidence: 67%
“…Two further decaying exponentials are included for LAB/PPO, based on [42]. The simulated time profile is:…”
Section: B Photon Productionmentioning
confidence: 99%
“…The targets are simulated using properties from [14,15,42,44,45]. The scintillation light yield is set to 1010 photons/MeV for LAB [44] and 10800 photons/MeV for LAB/PPO [15].…”
Section: Prospects With Liquid Scintillator Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large fraction of these decays can be identified (tagged) by making use of the fast decay time of LAB which allows for an α-β pulse shape discrimination [4]. For example, the internal decay of 214 Bi (Q ∼ 3.27 MeV) can be identified by the delayed coincidence with the 214 Po α decay for which the half-life is 164 μs.…”
Section: Lab Purification and Backgroundsmentioning
confidence: 99%